Pengaruh Cash Flow dan Profitabilitas Terhadap Cash Holding Perusahaan Property dan Real Estate - Rizky Camelia; Fajar Syaiful Akbar (Al-Buhuts, 2024)
This study examines the effect of capital expenditure, cash flow, leverage, and profitability on the company's cash holding. This research uses a quantitative approach method. The population in this study is all property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2020 – 2022. The sampling technique uses the purposive sampling method, with predetermined criteria obtained samples of 34 companies. The data used is secondary data obtained from the financial statements of the companies that are sampled. The data were analyzed using multiple linear regression analysis techniques with the help of SPSS 23 software. The result of this study is that profitability has a significant effect on cash holding because the significance level of profitability is 0.042 < 0.05 and t-stat value of 2.058 > 1.985 (table t value). Meanwhile, Capital expenditure has no effect because the significance level is 0.064 > 0.05 and the t-stat value is 1.873 < 1.985 (table t value). Cash flow does not affect cash holding because the significance level of cash flow is 0.977 > 0.05 and t-stat value is 0.029 < 1.985 (table t value). Leverage does not affect cash holding because the significance level is 0.101 > 0.05 and the t-stat value is -1.658 < 1.985 (table t value).